The Effects of Contextual Learning and Teacher's Work Spirit on Learning Motivation and Its Impact on Affective Learning Outcomes - Naziah, Risyatun; Caska, Caska; Nas, Syakdanur; Indrawati, Henny (Journal of Educational Sciences, 2020)
The goal of achieving student learning outcomes is not entirely only values in numbers or cognitive learning outcomes. But it also attaches great importance to the affective learning outcomes shown in attitudes or behavior. This study aims to analyze the effect of contextual learning approaches and teacher morale on learning motivation and its impact on student affective learning outcomes. The population in this study were 728 grade 8 students of SMP Negeri 20 and SMP Negeri 23 in Tampan. With the cluster random sampling technique a sample of 155 students was obtained. Data collection used a questionnaire then the data were analyzed by path analysis. The results found that contextual learning approaches have an influence on student motivation, the experience of working with friends while learning has an effect on student motivation and learning behavior, a positive effect on behavior is shown in attitudes manifested in affective domain learning outcomes. The work spirit of the teacher contributes to student affective learning outcomes, high teacher enthusiasm and the teacher's ability have an effect on student motivation to positively impact student affective learning outcomes.